1970
DOI: 10.1111/j.1365-2141.1970.tb01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Typing Using a Routine One‐Step Lymphocyte Separation Procedure

Abstract: A reliable rapid one-step method is described for the preparation of lymphocytes from 0.25 ml aliquots of defibrinated whole venous blood for tissuetyping. An average yield of 70% lymphocytes is obtained relatively free from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(49 citation statements)
references
References 4 publications
0
49
0
Order By: Relevance
“…Also, the spermidine-spermine ratio was similar in both groups. These data must almost entirely reflect the erythrocyte polyamine concentrations, since analysis of different blood cell fractions separated by a ficoll gradient procedure (10) showed that 95% of the blood polyamine was associated with erythrocytes. Blood plasma contained negligible amounts of polyamines, as reported previously ( 13).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the spermidine-spermine ratio was similar in both groups. These data must almost entirely reflect the erythrocyte polyamine concentrations, since analysis of different blood cell fractions separated by a ficoll gradient procedure (10) showed that 95% of the blood polyamine was associated with erythrocytes. Blood plasma contained negligible amounts of polyamines, as reported previously ( 13).…”
Section: Methodsmentioning
confidence: 99%
“…The lymphocytes were separated by using a gradient of density by the Ficoll-Hypaque technique (12). The lymphocytes were tested with antisera of 39 specificities: 18 of the A locus-I, 2, 3, 9, 10, I I , w23, w24, 25, 26, 28, 29, w30, w31, w32, w33, w34, w36; and 21 of the B locus -5, 7, 8, 13, 14, 15, 17, 18, w22, 27, w35, w38, w39, 40, w42, w44, w45, w49, w50, w51, w52.…”
Section: Methodsmentioning
confidence: 99%
“…Lymphocytes were therefore prepared by two methods-one involving glass wool filtration of the cells (Lichtman and Weed, 1970) and the second, a density separation using triosil/ficoll (Harris and Ukaejiofo, 1970). The volume of blood taken depended on the subject's white cell count; in the control subject up to 400 ml for method 1 and 150 ml for method 2 was required, whereas in the patients with chronic lymphatic leukaemia the maximum volume required for either method was 40 ml.…”
Section: Lymphocyte Isolationsmentioning
confidence: 99%